Pembelajaran Sejarah yang Monoton: Suatu Pembelajaran Tanpa Alternatif dalam Menghadapi Tantangan dan Tuntunan Zaman yang Berubah di SMA N 1 Ulakan Tapakis - Yuherman, Ulfa; Montessori, Maria; Nora3, Desri (Inovan Publisher, 2025)
The background of this study is about monotonous history learning conducted by history teachers teaching at SMA N 1 Ulakan Tapakis. The study aims to examine the reasons behind history teachers at SMA N 1 Ulakan Tapakis continuing to teach using the old model and seemingly ignoring the 21st-century student-centered learning model. The research approach used is qualitative research. There are three stages in the research, namely: (1) Pre-field stage, (2) Fieldwork stage, (3) Data analysis stage. The results of the research can be concluded that monotonous learning is caused by several reasons that are actually not too serious. The monotonous learning that occurs at SMA N 1 Ulakan Tapakis can be changed in the right direction if teachers are more enthusiastic in applying 21st-century learning models and if students are more emphasized with their learning responsibilities.